Effect of Tigecycline on Normal Oropharyngeal and Intestinal Microflora - Nord, Carl Erik (American Society for Microbiology, 2006)
Antibacterial agents disrupt the ecological balance of the normal human microflora. Tigecycline, a member of a new class of antibiotics (glycylcyclines), has been shown to have a potent broad-spectrum activity against most gram-positive and gram-negative aerobic and anaerobic bacteria. The aim of the study was to investigate the ecological effects of tigecycline on the normal oropharyngeal and intestinal microflora of healthy subjects. Thirteen healthy white subjects (six females and seven males) between 20 and 31 years of age received 100 mg of tigecycline in the morning on day 1 as a 30-min intravenous infusion followed by a 50-mg dose of tigecycline every 12 h as a 30-minute infusion for 10 days. One subject was withdrawn on day 2 because of an adverse event (urticaria). Serum, saliva, and fecal samples were collected before, during, and after administration for microbiological cultivation and for assays of tigecycline. All new colonizing bacteria were tested for susceptibility (resistance of ≥8 mg/liter) during the investigation period. The fecal concentrations on day 8 were from 3.0 to 14.1 mg/kg, with a mean value of 6.0 mg/kg and a median value of 5.6 mg/kg. The saliva concentrations were generally low (0 to 0.12 mg/liter). A minor effect on the oropharyngeal microflora was observed. The numbers of enterococci and Escherichia coli cells in the intestinal microflora were reduced at day 8 (P < 0.05), while those of other enterobacteria and yeasts increased. There was a marked reduction of lactobacilli and bifidobacteria (P < 0.05) but no impact on bacteroides. No Clostridium difficile strains were isolated. Two Klebsiella pneumoniae strains and five Enterobacter cloacae strains resistant to tigecycline were found on day 8.